Bottled Up : How the Way We Feed Babies Has Come to Define Motherhood, and Why It Shouldn't. - Cobb-Barston, Suzanne Michaels, 1978- (University of California Press, 2012)
As the subject of a popular web reality series, Suzanne Barston and her husband Steve became a romantic, ethereal model for new parenthood. Called "A Parent is Born," the program's tagline was "The journey to parenthood ... from pregnancy to delivery and beyond." Barston valiantly surmounted the problems of pregnancy and delivery. It was the "beyond" that threw her for a loop when she found that, despite every effort, she couldn't breastfeed her son, Leo. This difficult encounter with nursing-combined with the overwhelming public attitude that breast is not only best, it is the yardstick by.